Advances in the Preparation of Fluorinated Isoquinolines: A Decade of Progress - Joseph C. Sloop (Journal of Chemistry)
Heterocyclic molecules incorporating fluorinated isoquinoline components are found in many medicinally and agriculturally important bioactive products as well as industrially impactful materials. Within the past decade, a variety of isoquinolinic ring assembly techniques has enabled the introduction of diverse fluorine-containing functionalities which can enhance potential bioactivity and industrial utility. This review examines recent noncatalyzed and transition metal catalyzed synthetic approaches to the assembly of isoquinoline derivatives that are ring-fluorinated and/or result in the incorporation of fluorine-containing functional groups. Specifically, efficient synthetic methods and regioselectivity in the incorporation of functional groups into isoquinoline ring systems are examined.